Faktor-faktor yang telahmendorong graduan dan alumni Universiti Teknologi Malaysia menceburi bidang keusahawanan - Mohd. Osman, Mohd. Hassan (Faculty of Management and Human Resource Development, 2004)
The study identified factors that motivated UTM alumni's and graduates to be an entrepreneur. This research focused on four main factors i.e. namely entrepreneur background, motivation, attitude and skills. A set of questionnaire was distributed to 53 entrepreneurs who were UTM alumni. The study found that majority of the respondents agreed that attitude, motivation and skills, are the three most important factors influencing UTM graduate to be an entrepreneur. The study also found that majority of the entrepreneurs agreed that entrepreneur's background s not a major factor that influenced them to be an entrepreneur. Spearman correlation analysis was employed to determine the relationship between these influencing factors with three dimensions of entrepreneur achievement: i.e. capital investment, total sales and company assets. A number of hypotheses were tested and it was found that significant correlation between entrepreneur attitude and capital investment as well as entrepreneur skills and total sales. Finally, the study proposes ways to further develop entrepreneurship in Universiti Teknologi Malaysia